2015
DOI: 10.1038/cddis.2015.112
|View full text |Cite
|
Sign up to set email alerts
|

PD-1 and Tim-3 pathways are associated with regulatory CD8+ T-cell function in decidua and maintenance of normal pregnancy

Abstract: CD8+ T cells are critical in the balance between fetal tolerance and antiviral immunity. T-cell immunoglobulin mucin-3 (Tim-3) and programmed cell death-1 (PD-1) are important negative immune regulatory molecules involved in viral persistence and tumor metastasis. Here, we demonstrate that Tim-3+PD-1+CD8+ T cells from decidua greatly outnumbered those from peripheral blood during human early pregnancy. Co-culture of trophoblasts with CD8+ T cells upregulated PD-1+ and/or Tim-3+ immune cells. Furthermore, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
131
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(139 citation statements)
references
References 38 publications
4
131
0
4
Order By: Relevance
“…Specifically, HLA-G can present with nonamer peptides and bind CD8 in an analogous manner to classical HLA-class I proteins, facilitating the escape of immune surveillance (alloreactivity) by host T-lymphocytes and NK-cells[28,29]. Since PD-1 positive lymphocytes were detected in many of gestational trophoblastic disease (GTD) tissues as in a normal placental site [30], it is likely that PD-L1 expressing syncytiotrophoblast works in conjunction with HLA-G expressing intermediate trophoblastic cells to shield the entire gestational sac and fetus from attack by maternal immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, HLA-G can present with nonamer peptides and bind CD8 in an analogous manner to classical HLA-class I proteins, facilitating the escape of immune surveillance (alloreactivity) by host T-lymphocytes and NK-cells[28,29]. Since PD-1 positive lymphocytes were detected in many of gestational trophoblastic disease (GTD) tissues as in a normal placental site [30], it is likely that PD-L1 expressing syncytiotrophoblast works in conjunction with HLA-G expressing intermediate trophoblastic cells to shield the entire gestational sac and fetus from attack by maternal immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike conventional cytotoxic CD8 + T cells in peripheral tissues, CD8 + T cells in decidual tissue are important for providing protective immunity and secreted cytokines in early pregnancy to promote the development of the fetus. These CD8 + T cells are considered to be regulatory or suppressor CD8 + T cells, co-expressing PD-1 and Tim-3 (Wang et al, 2015). CD4 + effector T cells, particularly the recently described Th17 cells, may play an important role in the pathogenesis of URSA (Wang et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These CD8 + T cells are considered to be regulatory or suppressor CD8 + T cells, co-expressing PD-1 and Tim-3 (Wang et al, 2015). CD4 + effector T cells, particularly the recently described Th17 cells, may play an important role in the pathogenesis of URSA (Wang et al, 2015). It has been reported that the proportion of Th17 cells, the Th17-inducing cytokine IL-23, and RAR-related orphan receptor C (RORC), an essential transcription factor in Th17 cells, are higher in decidual tissue from URSA patients compared to normal pregnant controls (Wang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While CD8 T cells and be modified by pregnancy, they still can attack fetal cells in the maternal blood and lymphoid organs 105, 106 . In contrast, and adding to the paradigm that T reg support maternal tolerance, is the observation that pregnancy can support the generation of CD8 T reg 99, 107 , which may modify CD8 T cell cytotoxicity during pregnancy.…”
Section: Adaptive Immunitymentioning
confidence: 99%